Heat transfer to non-Newtonian fluids : fundamentals and analytical expressions - Shenoy, Aroon V., 1951- (Weinheim, Germany : Wiley-VCH, 2018)
This title has been written with the idea of providing the fundamentals for those who are interested in the field of heat transfer to non-Newtonian fluids.
Fluid; 11.11 Pure Darcy Transient Natural Convection From Vertical Flat Plate Embedded In A Porous Medium with a Power-Law Fluid; 11.12 Pure Darcy Transient Natural Convection From Vertical Flat Plate Embedded In A Porous Medium with a Herschel-Bulkley Fluid; 11.13 Oscillatory Natural Convection in a Viscoelastic Oldroyd Fluid in Densely Packed Horizontal Porous Layers; ; Nomenclature; References; Index.
Includes bibliographical references.
Vendor-supplied metadata.
Keywords: Heat -- Transmission; Non-Newtonian fluids; TECHNOLOGY & ENGINEERING -- Mechanical; Heat -- Transmission; Non-Newtonian fluids; Electronic books